Efficacy of post-exercise recovery strategies for elite soccer players: a network meta-analysis - Liu, Jie; Li, Qiang; Han, Yu (Frontiers in Physiology, 2026)
ObjectiveThis study aimed to systematically compare the efficacy of various recovery strategies for improving neuromuscular function, muscle damage, and subjective fatigue in elite soccer players following matches or validated simulations, and to provide evidence-based guidance for clinical practice.MethodsFollowing PRISMA-NMA guidelines, we systematically searched PubMed, Embase, Cochrane Library, Web of Science, and Scopus for randomized controlled trials evaluating post-match or post-simulation recovery strategies in professional and semi-professional soccer players. A Bayesian random-effects model was applied to conduct the network meta-analysis. Effect sizes were reported as mean differences (MD) with 95% credible intervals (CrI), and intervention efficacy was quantified using Surface Under the Cumulative Ranking (SUCRA) values.ResultsTwenty-three RCTs involving 388 participants and 17 recovery interventions were included. Key findings were as follows: (1) Far-infrared therapy (FIR) was most effective in improving Countermovement jump (CMJ) height (SUCRA = 98.3%); (2) Intermittent negative pressure therapy (INPT) produced the greatest reduction in Creatine kinase (CK) levels (SUCRA = 91.0%); (3) Portable cold compression therapy (PCMcold) had the strongest effect on alleviating Muscle soreness (MS) (SUCRA = 98.9%); (4) FIR and Intermittent vascular occlusion (IVO) significantly improved Maximal voluntary contraction (MVC), although Hyperoxic gas (Hyp) ranked highest (SUCRA = 89.8%); and (5) no intervention significantly improved 20-m sprint performance (all 95% CrI included zero), and although IVO ranked first (SUCRA = 84.5%), its evidence reliability was low.ConclusionPersonalized post-match recovery in elite soccer should be based on specific targets. FIR is recommended for CMJ restoration, INPT for muscle damage repair, PCMcold for reducing subjective soreness, and FIR may be considered for MVC recovery. No superior intervention was identified for 20-m sprint recovery; therefore, basic recovery measures are advised. Future multi-arm RCTs are required to validate combined recovery strategies and standardize intervention parameters.